Very Hungry Caterpillar - Carle, Eric (London Penguin Books Ltd, 2005)
Eric Carle's classic The Very Hungry Caterpillar, with an enclosed CD. This is a book and CD pack of the best selling picture book, The Very Hungry Caterpillar. There is a straight reading of the story first with intro and exit music and then a reading that includes a 'ping' to turn the page. Eric Carle is an internationally bestselling and award-winning author and illustrator of books for very young children. Eric lives in Massachusetts with his wife, Barbara. The Carles opened The Eric Carle Museum of Picture Book Art in Massachusetts in 2002. Don't miss all the other Very Hungry Caterpillar and Eric Carle books: The Very Hungry Caterpillar; Eric Carle's Very Special Baby Book; Polar Bear, Polar Bear, What do You Hear?; The Very busy Spider; The Very Quiet Cricket; The Artist Who Painted a Blue Horse; 1, 2, 3 to the Zoo; Baby Bear, Baby Bear, What do you See?; The Very Hungry Caterpillar Pop-Up Book; Polar Bear, Polar Bear, What Do You Hear?; The Very Hungry Caterpillar's Buggy Book; Brown Bear, Brown Bear, What Do You See?; The Bad-Tempered Ladbybird; The Very Hungry Caterpillar: Little Learning Library; The Very Hungry Caterpillar: Touch and Feel Playbook; My Very First Book of Words; The Very Hungry Caterpillar Book and Toy; Little Cloud; Today is Monday; My Very First Book of Shapes; The Very Hungry Caterpillar's Sound Book; The Very Hungry Caterpillar; From Head to Toe; The Very Hungry Caterpillar Big Board Book; Draw Me a Star; Mister Seahorse; Do You want to be My Friend?; The Tiny Seed
English stories
2
Keywords: English stories